Ecological Test of New Varieties of Fine Fiber Cotton - Danabayev Abdumurat Berdiyevich; Bobayarov Khidir Jumanazarovich; Khushbokova Farangiz Ilhomovna (Zien Journals, 2023)
The article presents the results of ecological testing of new varieties of thin fiber cotton at the Scientific Research Institute of Fine Fiber Cotton .
Keywords: Cotton varieties; new varieties; ecological test; G. barbadense L. and G. hirsutum L